Intrinsic Versus Extrinsic Motivation in Logistics: A Quantitative Analysis of Performance Outcomes - Budiyanto, Albert; Masito, Fitri; Toja, Andi Batari (Indonesian Scientific Publication, 2024)
Employee motivation is a critical determinant of organizational performance, particularly in logistics warehousing where efficiency and resilience are paramount. This study investigates the influence of intrinsic and extrinsic motivation on employee performance at PT Aerojasa Cargo using Herzberg’s two-factor theory as a framework. A quantitative survey was conducted with 55 employees selected from 120 using Slovin’s formula. Motivation (knowledge, skills, rewards, behavioral direction, persistence) and performance (accuracy, timeliness, quality, quantity, neatness) were measured through a 5-point Likert-scale questionnaire, and data were analyzed using SPSS 26. Regression analysis revealed a strong correlation (R² = 0.833, p < 0.05), with intrinsic factors such as persistence and recognition emerging as the strongest predictors of performance, surpassing extrinsic motivators like salary. These findings provide robust empirical evidence of the relevance of Herzberg’s theory in Indonesia’s logistics sector and underscore the need for HR strategies that prioritize intrinsic motivators. Practical contributions include designing recognition systems, training, and career development programs to enhance employee persistence and behavioral alignment.